If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8-(13+4x)=-3(5-9x)+2
We move all terms to the left:
-8-(13+4x)-(-3(5-9x)+2)=0
We add all the numbers together, and all the variables
-(4x+13)-(-3(-9x+5)+2)-8=0
We get rid of parentheses
-4x-(-3(-9x+5)+2)-13-8=0
We calculate terms in parentheses: -(-3(-9x+5)+2), so:We add all the numbers together, and all the variables
-3(-9x+5)+2
We multiply parentheses
27x-15+2
We add all the numbers together, and all the variables
27x-13
Back to the equation:
-(27x-13)
-4x-(27x-13)-21=0
We get rid of parentheses
-4x-27x+13-21=0
We add all the numbers together, and all the variables
-31x-8=0
We move all terms containing x to the left, all other terms to the right
-31x=8
x=8/-31
x=-8/31
| 4x+1=0x+6 | | 3x-5(x-4)=-5+2x-9 | | 3x-5(x-4)=-5+2x-5 | | 119+2x+x+21.5=180 | | 15-d=4 | | 7x+28+33=180 | | 3a^2-5a+1=0 | | (x+14)x=20.7 | | Y=0.00005x^2-0.06x | | 49+4y=-9 | | 26+2x-14=90 | | x2=-427 | | (7+35)7=x2 | | 12(y+1)=16(21) | | 4-3q=22 | | −2x+15=−24 | | -27=5d+3 | | 3x+38+x=90 | | 150=-0.43x+405 | | -24=−24-12x | | 4x+5x=12x | | (10+22)10=(13+x)13 | | -24=−24-12b | | 3(x-2)+5x+7=7x-2(x+4) | | x-(9/2)=11 | | x+2/3+x=1-3/4x | | y=-0.43150+405. | | 25.3-7.5x=101.8 | | (3-2x)+3(1-4x)-4(1-5x)=2(1-3x.) | | 4u/7=-20 | | 4q=–44 | | 3/4m=39/4 |